XBP1 activation enhances MANF expression via binding to endoplasmic reticulum stress response elements within MANF promoter region in hepatitis B. (June 2018) - Wang, Dong; Hou, Chao; Cao, Yajie; Cheng, Qiyao; Zhang, Li; Li, Hong; Feng, Lijie; Shen, Yuxian
Graphical abstract: Highlights: MANF is positively correlated with ER stress. Activation of IRE1α-XBP1 pathway promotes MANF transcription via ERSE I. MANF is potential to regulate its own transcription through binding to XBP1s. Abstract: As an endoplasmic reticulum (ER) stress-related protein, mesencephalic astrocyte-derived neurotrophic factor (MANF) is involved in inflammatory diseases, such as rheumatoid arthritis. However, the mechanisms of the transcriptional regulation of MANF is still undefined. Here, we showed that MANF expression was upregulated in hepatitis B tissues and hepatoma cells, and positively correlated with the spliced X-box binding protein-1 (XBP1s). Both overexpression of XBP1s and tunicamycin treatment were able to enhance MANF transcription. On the contrary, inhibition of XBP1 splicing by IRE1α endonuclease inhibitor or knockdown of XBP1s with siRNA attenuated MANF expression. Two ER stress-responsive elements (ERSE) were found in the promoter region of MANF (ERSE I and ERSE II). The chromatin immunoprecipitation and reporter gene assay showed that XBP1s mainly binds to ERSE I to promote MANF transcription. Moreover, MANF was found to interact with XBP1s to enhance its own expression. Our findings uncover a new mechanism of ERSE-dependent transcriptional regulation of MANF, as well as a key role of XBP1s in promoting the MANF expression.